Byzantium and the Avars, 6th-9th century AD : political, diplomatic and cultural relations - Kardaras, Geōrgios Th., 1973- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2019)
In this book, Georgios Kardaras offers a global view of the contacts between the Byzantine Empire and the Avar Khaganate, emphasizing the reconstruction of these contacts after 626 (when, in contrast to archaeological evidence, written sources are very few) and the definition of the possible channels of communication between the two powers. The author scrutinizes the political and diplomatic framework, and critically examines issues such as mutual influence on material culture and on warfare, reaching the conclusion that significant contact between Byzantium and the Avars can be proved up until 775.